Análise funcional da ativação e da expressão do receptor da progesterona em cultura primária de células endometriais de pacientes portadoras de endometriose profunda intestinal - Kamergorodsky, Gil [UNIFESP] (2017)
OBJECTIVES: To evaluate the activation and expression of the progesterone receptor in primary culture of endometrial cells, after exposure to estradiol and progesterone. DESIGN: In vitro experimental study for analysis of microphysiometry and real-time PCR PLACE OF DEVELOPMENT: Pelvic Algeal and Endometriosis Sector and Center for Cellular and Molecular Therapy of UNIFESP / Escola Paulista de Medicina PATIENTS AND METHODS: This study included 20 patients, 11 with radiological diagnosis of deep intestinal pelvic endometriosis, confirmed by laparoscopy, and 09 without endometriosis. Endometrial fragments were obtained by means of a Novak® curette, later processed for culture formation. The culture plates were treated with 17-E2 and progesterone, and then processed for microphysiometry and real-time PCR. RESULTS: There was a decrease in nuclear expression of progesterone receptor (PR) mRNA after hormone treatment; six times lower in the deep endometriosis group than in the control group. In the microphysiometry study, mean ECARs (56.19 ± 0.76 μV / second) were lower than the control group (114.3 ± 1.34 μV / second) ). (P <0.005) CONCLUSIONS: Lower extracellular acidification and lower progesterone receptor expression were observed in endometrial stromal cells in culture compared to women without the disease. These findings support the hypothesis that resistance to progesterone may be involved in the etiopathogenesis of endometriosis.